2021
DOI: 10.47191/ijcsrr/v4-i5-12
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Emerging As an Opportunistic Pathogen

Abstract: Due to the re-emergence of infectious diseases, the causative pathogenic microorganisms are becoming the major microbiologic public health threat. It seems to be difficult to control the emergence of new and severe bacterial diseases. However, efforts are continuously being made to identify the main cause to prevent the uncontrolled spread of emerging diseases. This review focuses on emerging bacterial diseases and their causative bacteria and the pathway of pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Our investigations showed that silkworms fed an artificial diet were more likely to acquire bacterial diseases than those fed a mulberry leaf diet. Generally, an opportunistic pathogen does not harm its host; however, when the host’s resistance is low, it can cause disease ( 31 ). For example, Staphylococcus aureus can colonize the human nose asymptomatically and be transmitted from person to person without causing disease, thereby establishing long-term residence ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our investigations showed that silkworms fed an artificial diet were more likely to acquire bacterial diseases than those fed a mulberry leaf diet. Generally, an opportunistic pathogen does not harm its host; however, when the host’s resistance is low, it can cause disease ( 31 ). For example, Staphylococcus aureus can colonize the human nose asymptomatically and be transmitted from person to person without causing disease, thereby establishing long-term residence ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…C. perfringens was isolated from a broad range of environments, such as the soil, freshwater sediment, and the gastrointestinal track of human and animals ( 2 ). As an opportunistic pathogen [opportunistic pathogen is one that generally does not harm its host but can when the host's resistance is low ( 3 )], C. perfringens can cause disease; it causes a range of histotoxic and enteric diseases in humans and animals ( 4 ). C. perfringens bacteria are one of the most common causes of foodborne illness (food poisoning).…”
Section: Introductionmentioning
confidence: 99%